Performance of deamidated gliadin peptide antibodies as first screening for celiac disease in the general pediatric population - Al-Hussaini, Abdulrahman; Al-Jurayyan, Abdullah; Alharbi, Sahar; Salman Bashir, Muhammed; Troncone, Riccardo (Frontiers in Pediatrics, 2023)
Celiac serology has evolved, with the identification of newer antibodies against deamidated gliadin peptides (anti-DGP, IgA and IgG types) with sensitivity and specificity in detecting celiac disease (CeD) that are equivalent to anti-tissue transglutaminase (anti-TTG IgA)-based tests, particularly in populations with high pre-test probability of CeD (prevalence of CeD > 50% of the population under study). This opens the possibility that anti-DGP assays can be used to identify CeD in general population where prevalence of CeD is very low (≈ 1%).(1) To determine diagnostic performance of DGP antibodies-based serologic assays in identifying CeD during screening of general population and (2) to compare the levels of anti-DGP antibodies among CeD patients with mild and severe degrees of enteropathy.Serology tests for DGP Abs (DGP-IgA, DGP-IgG, and conjugate TTG/DGP antibodies) were performed on 104 serum samples of positive TTG-IgA (100 confirmed and 4 potential celiac cases) and a randomly selected 1000 negative TTG-IgA serum samples collected during mass screening of children (6-15 years) in 2014-2015.Sera from 32 of 1000 TTG-IgA negative serum specimens (3.2%) tested positive for one or more of the 3 anti-DGP serology tests. Thirteen of the 32 anti-DGP seropositive cases had positive result on follow up samples in 2020 (1.3%). Eight of the 13 underwent endoscopy with biopsies; only 2 had confirmed CeD (both DGP-IgG positive) (0.2%). The sensitivity and specificity of the serology assays were as following: DGP-IgA (62.7%, 40%); DGP-IgG (80.4%, 100%); conjugate TTG/DGP (96%, 10%). Based on receiver operating characteristic curves, the area under the curve for DGP-IgG [0.919; 95% CI -0.00406 to 0.114] was comparable to TTG-IgA [0.974; 95% CI 0.924 to 0.995] (P = 0.0679). Titers of antibodies to DGPs were higher in children with severe intestinal damage than in those with mild lesions (P < 0.001).The TTG-IgA assay remains the most reliable screening serology test for CeD in mass screening studies. By adding DGP-IgG to the mass screening protocol, the performance of TTG-IgA has improved marginally. In CeD patients detected by mass screening, the anti-DGP antibodies titer was higher among patients with severe degree of enteropathy as compared to the group with mild enteropathy.